Dry Eye Due To Millet Diabetes - Febriya Moestafa, Rizka (Jurnal KESANS : Kesehatan dan Sains, 2021)
Eye dry syndrome or dry eye is a multifactorial disorder that causes reduced tear fluid, causing discomfort to the eye. Several risk factors that cause dry eye such as history of medication, meibomian gland dysfunction, age, gender, systemic disease and immune disorders (Mark, et al., 2021). Diabetes mellitus is one of the risk factors for dry eyes. The International Dry Eye Workshop II (DEWS) divides dry eyes into two parts based on etiopathological criteria, namely due to lack of tear production or Aqueous Tear Deficiency (ATD) and excessive evaporation or Evaporative Tear Deficiency (ETD) (shimazaki, 2018). Prevalence This article aims to review Diabetes Miletus, one of the risk factors for dry eye. The source search was carried out on the online portal of the publication of the journal Nation Center for Biotechnology Information / NCBI, Google Scholar with the keywords "Eye Dry Syndrome, Diabetes Milletus, Eye Dry treatment".